Microarrays: bioassay performance on waveguide sensors and commercial capture surfaces - Wu, Peng, author; Grainger, David W., advisor; Parkinson, Bruce A., committee member; Meersmann, Thomas, committee member; Shi, Yian, committee member; Dandy, David S., committee member (Colorado State University. Libraries, 2006)
Microarray technology allows for large-scale parallel analysis of thousands of parameters within a single experiment, representing a revolution in the field of both genomics and proteomics. While the DNA microarray has been extensively used in gene expression and genotyping studies during the past decade, protein microarrays are still in their early development stage mainly due to the fact that protein molecules are inherently more complex than DNA and respond to these microassay formats much differently. For both DNA and protein microarrays, substantial problems and challenges remain to obtain reliable, clinically useful formats, including microarray surface preparation, microarray agent printing/immobilization, on-array capture assay selectivity and reproducibility, and signal detection sensitivity. The objective of this dissertation research is to investigate bioassay performance of nucleic acid and protein microarrays on various substrate surfaces including a silicon nitride waveguide sensor surface, model gold and commercial microarraying slides, providing new insight into the surface chemistry influences on DNA and protein immobilization during microarray printing, influences of different hydroxylated additives in antibody microarray performance, and the relationship between surface capture feature size and analyte flux (surface capture efficiency). New silicon nitride optical microfarbicated waveguide surfaces were silanized and modified with an organic hetero-bifunctional crosslinker. DNA oligonucleotides, streptavidin and murine anti-human interleukin-1β capture agents were successfully printed onto chemically modified silicon nitride surface in microarray formats, demonstrated by surface capture assays. X-ray photoelectron spectroscopy (XPS) was used to characterize each reaction sequence on the native silicon oxynitride surface. Various hydroxylated additives were added to capture antibody print buffers at different concentrations to stabilize printed antibodies during normal array spot dessication on commercial polymer-coated microarraying slides. Polyvinyl alcohol addition to print buffers produced the most regular spot morphologies, homogenous intra-spot antibody distribution, uniform fluorescence intensity, and improved analyte capture activity, maintaining capture activity against model analytes (anti-human IL-1β, IL-4 and TNFα) on these microarraying slides for up to 1 month under 4°C, dry storage conditions. Experimentally derived immobilized ligand and target capture densities as a function of microspot size for DNA probe oligomers on model gold substrates are compared directly with theoretical mass-transfer analysis, validating the inverse relationship between analyte flux and capture feature size under mass transfer limiting capture conditions that characterize many such assay formats.
Keywords: analytical chemistry; biochemistry